Multinationals and plant exit: evidence from Chile - Roberto Álvarez Espinoza; Holger Görg (Institute for the Study of Labor (IZA), 2005)
This paper examines the link between multinational enterprises and plant exit in Chile. We investigate three main questions: are affiliates of foreign multinationals more likely to exit than domestic firms? Does the exit probability of multinationals depend on its export orientation?, and Does the presence of multinationals affect the survival of other firms in the economy? Our results show that foreign plants are more likely to exit the economy, controlling for other firm and industry characteristics, only during the late 1990s, a period when the Chilean economy experience a massive slowdown. Our data also suggest that only domestic market oriented multinationals responded to this negative shock by being more footloose; this is not true for multinational exporters. We also find that the presence of multinationals has a positive effect on plant survival in the early 1990s. This positive effect, however, is fully captured by productivity, once controlling for TFP in our exit regressions we do not find any further impact of multinational presence on a plant's probability of exit.
Keywords: 330